Pengaruh Metode Board Rush Terhadap Peningkatan Kemampuan Berpikir Kritis Siswa Kelas V Dalam Pembelajaran IPAS DI SDN 17 Bajoe Kabupaten Bone - Sri Huldania; Rosmalah; Awaluddin Muin (MACCA : Science-Edu Journal, 2026)
This study is a pre-experimental study that aims to determine the effect of the Board Rush method on improving the critical thinking skills of fifth-grade students in science learning at SDN 17 Bajoe, Bone Regency. The research design used is One-Group Pretest-Posttest Design. The population in this study were all fifth-grade students of SDN 17 Bajoe, Bone Regency with a sample of 27 students selected using saturated sampling techniques. The data collection technique used was a test (pretest and posttest) in the form of essay questions to measure students' critical thinking skills before and after the application of the Board Rush method. Data analysis techniques used descriptive statistics and inferential statistics. The results of the descriptive statistical analysis showed that the average pretest score of students' critical thinking skills was in the very low category with a value of 51.74 and experienced an increase in the average posttest score of 84.00 which was in the high category. This increase indicates a change in students' critical thinking skills after the application of the Board Rush method in science learning. Based on the results of inferential statistical analysis using paired samples t-test, a significance value (Sig. 2-tailed) of 0.001 < 0.05 was obtained, which means there is a significant difference in students' critical thinking abilities before and after the application of the Board Rush method. Because the average posttest score is higher than the average pretest score and the results of the hypothesis testing show a significant difference, it can be concluded that the Board Rush method has an effect on improving the critical thinking abilities of fifth-grade students of SDN 17 Bajoe, Bone Regency.